1999
DOI: 10.1111/1467-9280.00148
|View full text |Cite
|
Sign up to set email alerts
|

Hale-Bopp and Handedness: Individual Differences in Memory for Orientation

Abstract: The accuracy with which a person recalls the orientation of a human figure or head has been shown to depend systematically on the person's handedness. This study investigated whether memory for the orientation of an inanimate object displays a similar effect. In contrast to previous work investigating memory for depictions encountered over many years, the present work focused on memory for a unique event that engaged considerable attention over a relatively brief period-Comet Hale-Bopp. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…But in addition, left-facing heads were also used as stimuli and found to be more likely to be correctly recognized by right-handed than by left-handed participants. Consistent with this, it has been shown that right-handed people are also more likely than left-handed people to recall correctly that the head of a comet faced to the left (Martin & Jones, 1999). Thus, overall, there was a significant interaction here between recognition of left-facing and right-facing heads by left-handed and right-handed participants.…”
Section: Discussionsupporting
confidence: 61%
“…But in addition, left-facing heads were also used as stimuli and found to be more likely to be correctly recognized by right-handed than by left-handed participants. Consistent with this, it has been shown that right-handed people are also more likely than left-handed people to recall correctly that the head of a comet faced to the left (Martin & Jones, 1999). Thus, overall, there was a significant interaction here between recognition of left-facing and right-facing heads by left-handed and right-handed participants.…”
Section: Discussionsupporting
confidence: 61%
“…There is some evidence that handedness is associated with differences in the ways that people see and interpret the world. For example, Martin and Jones (1999) found that handedness affects memory for the orientation of objects. The comet Hale-Bopp's orientation, as viewed by experiment participants, would have been facing downward to the left, meaning that the comet's head was to the viewer's left, and the tail would trail behind to the viewer's right.…”
Section: Internal Factorsmentioning
confidence: 99%
“…Several studies report that right-handers tend to recall familiar human figures (e.g., on road signs or coins) as facing left, whereas left-handers tend to recall the figures as facing right (Jones, 1990;Martin & Jones, 1998, 1999Rubin & Kontis, 1983). The effect has also been observed for memory for the direction of the Hale-Bopp comet, indicating that the stimuli need not be human (Martin & Jones, 1999). The authors suggested that the handedness effect is mediated by motoric processes that would be used for drawing.…”
Section: Motoric Influences On Perceptual Representations Of Human Fi...mentioning
confidence: 99%